Implementation and control of a hybrid voltage gain transformer-less DC-DC converter - Azan Bin Asbi (Nanyang Technological University, 2024)
In this report, the design, implementation, and control of a hybrid non-isolated boost converter using an output feedback controller are presented. The converter topology is formed by a voltage multiplier and a switched capacitor using two-inductor boost converter with two capacitor banks. The converter is implemented on a breadboard for validity test and then constructed on a universal PCB for a proper evaluation. The output feedback controller is implemented on a breadboard. Experimental results are given to illustrate the features of the controller.